Niemandsland : a history of unoccupied Germany, 1944 - 1945 - Pritchard, Gareth (Cambridge Univ. Press, 2012)
Machine generated contents note: Introduction; 1. The antifascist committees; 2. Conflict communities of the western Erzgebirge; 3. Into the abyss; 4. Taking power in Niemandsland; 5. Surviving in Niemandsland; 6. The politics of antifascist rule; 7. Antifascists and the wider population; 8. The politics of Soviet occupation; 9. Lessons of Niemandsland